THE EFFECT OF MOTIVATION ON JORDANIAN 10TH GRADE STUDENTS’ WRITING SKILL IN ENGLISH - Al- Shourafa, Areej (European Scientific Journal, ESJ, 2012)
This study aimed to investigate the effect of motivation on English writing skills among Jordanian 10th grade students in Al-karak Directorate of Education during the second semester 2011\2012. The sample of the study consisted of (198) male and female students, which was stratified randomly selected from Alkarak secondary school for boys and Alkarak secondary school for girls . The researcher developed a questionnaire where reliability and validity of the instrument were ensured . The results of the study indicated that there were statistical significant differences at(α≤ 0.05) between external and internal motivation due to gender variable. and that there were statistical significant differences at (α≤ 0.05) in the level of extrinsic and intrinsic motivation among 10th grade students due to the level of motivation.